Comparison of auditory hallucinations across different disorders and syndromes. (February 2012) - Sommer, Iris EC; Koops, Sanne; Blom, Jan Dirk
SUMMARY  Auditory hallucinations can be experienced in the context of many different disorders and syndromes. The differential diagnosis basically rests on the presence or absence of accompanying symptoms. In terms of clinical relevance, the most important distinction to be made is between auditory hallucinations occurring in the context of psychotic disorders and those that are due to a somatic disorder. Auditory hallucinations are also quite common in otherwise healthy individuals and are therefore not necessarily disease-related. As auditory hallucinations are often accompanied by hallucinations in other modalities, pinpointing the modality in which hallucinations are experienced most frequently may provide a first – albeit coarse – indication of whether the auditory hallucinations are part of a neurological disorder (mainly visual), a psychiatric disorder (mainly auditory), an ear disorder (mainly auditory) or whether they occur in the absence of any disorder (mainly auditory). Epilepsy is the most important exception to this coarse differentiation. Another traditional distinction between hallucinations occurring in the context of neurological and psychiatric disorders is that the former are assumed to start at an advanced age, whereas hallucinations in the context of psychiatric disorders typically begin in late adolescence or early adulthood. Although there are many exceptions to this rule of thumb – as in psychotic depression, late-onset schizophrenia and epilepsy – age of onset can still be a valuable clinical indicator. The content of auditory hallucinations is notoriously unreliable for differential diagnosis and the safest way to an accurate diagnosis rests with the detection of psychiatric and somatic comorbid symptoms.